2019
DOI: 10.33963/kp.14964
|View full text |Cite
|
Sign up to set email alerts
|

Del Nido cardioplegia as a safe and effective method of myocardial protection in adult patients undergoing cardiac surgery: a single‑center experience

Abstract: Background Del Nido (DN) cardioplegia is increasingly popular in adult cardiac surgery. It allegedly allows for up to 90 minutes of safe myocardial ischemia with a single dose. aims We aimed to evaluate the benefits of DN cardioplegia. methods Of the 2108 patients undergoing coronary or heart valve surgery with the use of cardiopulmonary bypass (CPB) between January 1, 2016, and September 30, 2017, 1236 (59%) received DN and 872 (41%) received cold blood cardioplegia. We retrospectively analyzed the collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 12 publications
0
18
0
1
Order By: Relevance
“…Twenty-nine (29) studies were included in this systematic review and meta-analysis: three RCTs [4,14,15], two prospective observational non-randomised studies [16,17], 16 PMCS [7,8,[18][19][20][21][22][23][24][25][26][27][28][29][30][31], and eight unmatched retrospective cohort studies [5,6,[32][33][34][35][36][37] (Table 1). The majority of the studies used blood cardioplegia in a ratio of 4:1 (blood:crystalloid), with one study using an 8:1 ratio [29], and another study using only blood [4].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-nine (29) studies were included in this systematic review and meta-analysis: three RCTs [4,14,15], two prospective observational non-randomised studies [16,17], 16 PMCS [7,8,[18][19][20][21][22][23][24][25][26][27][28][29][30][31], and eight unmatched retrospective cohort studies [5,6,[32][33][34][35][36][37] (Table 1). The majority of the studies used blood cardioplegia in a ratio of 4:1 (blood:crystalloid), with one study using an 8:1 ratio [29], and another study using only blood [4].…”
Section: Resultsmentioning
confidence: 99%
“…The supplementary use of terminal warm blood cardioplegia achieved prolongation of the safe ischemic time up to 120 minutes for a single-dose application [18]. Kuciński J., (2019) found that Del Nido allows for up to 90 minutes of safe myocardial ischemia with a single dose compared with cold blood cardioplegia, as shown by lower troponin T release [19].…”
Section: Discussionmentioning
confidence: 99%
“…6,16 Kucinski and colleagues recently reported superiority for del Nido, when troponin values were measured as an isolated value the morning after surgery. 9 Ad and colleagues reported no significant difference in Troponin I values within 24 h of surgery. 3 The magnitude of troponin rise after cardiac surgery represents the sum of multiple sources of injury, including the level of injury prior to the patient arriving in the operating room, those made during cardiotomy for cannulation, exposure and incision of cardiac chambers and coronary arteries, myocardial ablation for treatment of arrhythmias, and myocardial cell injury due to ischaemia.…”
Section: High-sensitivity Troponin Tmentioning
confidence: 96%
“…[4][5][6][7] The existing reports investigating post-operative troponin values for patients receiving del Nido have focused on the first 24 h post-operatively, and had small numbers of patients. [8][9][10][11] Following the introduction of del Nido into our practice, we sought to confirm equivalence of technique based upon clinical markers of myocardial protection, and hs-TnT profiles up to 72 h post-operatively, in two cohorts of patients receiving either del Nido or hyperkalemic blood cardioplegia.…”
Section: Introductionmentioning
confidence: 99%